Design and implementation of microstrip filters for a radio over fiber network demonstrator - Rocha, Paulo R. F. (2012)
Dissertação de mest., Engenharia Eléctrica e Telecomunicações, Faculdade de Ciências e Tecnologia, Univ. do Algarve, 2010